PENGARUH KNOWLEDGE MANAGEMENT DAN INOVASI TERHADAP KEUNGGULAN KOMPETITIF BERKELANJUTAN MELALUI STRATEGI BISNIS DI UMKM KABUPATEN BATANG, JAWA TENGAH - Faradista Sekar Nagari; Indi Djastuti (Jurnal Akuntansi dan Pajak, 2023)
UMKM have contributed to the movement of the regional economy in reducing the unemployment rate. However, the weak points that are quite prominent in Small and Medium Industries (IKM) in Indonesia include a number of things including market orientation, resources, especially human resources, market access, capital and mastery of technology (OEDC, 2004). Therefore, the importance of a Knowledge Management (KM) system is expected to help an organization strive to maximize work efficiency in order to face the challenges of competition with competitors and can also create an inovasi in the form of products or services owned by the organization. In addition, having a strategy and focus in business is very important for the success of the company. Strategi bisnis will help companies determine between good and bad decisions. The type of research used is explanatory research. The research data consists of primary data and secondary data. In this study, data collection was carried out including: library research, observation, distribution of questionnaires. The sampling technique used is purposive sampling. Data analysis technique uses Partial Least Square (PLS). The results of the study prove that Knowledge Management has a significant positive effect on Keunggulan kompetitif berkelanjutan, Knowledge Management has a significant positive effect on Strategi bisnis, Strategi bisnis mediates the influence of Knowledge Management on Keunggulan kompetitif berkelanjutan, Innovativeness has a significant positive effect on Strategi bisnis, Innovativeness has a significant positive effect on Keunggulan kompetitif berkelanjutan.. Keywords : Knowledge Management; Innovativeness; Keunggulan kompetitif berkelanjutan; Strategi bisnis.